PENGARUH MOTIVASI, KEMAMPUAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PT PEGADAIAN (PERSERO) KANWIL II PEKANBARU - Widodo, R.Swasono Amoeng (Jurnal Tepak Manajemen Bisnis, 2014)
This study aimed to determine the effect of variable Motivation, Ability and Environmentalsimultaneously and partially on performance in PT Pegadaian (Persero) Regional Office II Pekanbaru. On thebasis of these objectives, the variable motivation, ability, and Work Environment is the independent variable andthe dependent variable is employee performanceMotivation by influential categorized summary table where as many as 48 people or 50.50% stated Influential(B) and 13 people or 13.70% said no impact. This means that the respondents agree that motivation influentialin PT Pegadaian (Persero) Regional Office II Pekanbaru. This result is in line with the respondents who statedthat the results of the regression variable motivation (X1) significantly affects the performance PT Pengadain(Persero) Regional Office II Pekanbaru.Based on the Work Environment of respondents according to the recapitulation of respondents categorized effectwhere as many as 54 people or 56.80% stated Agree (S) and 8 people or 8.40% did not agree.Work on the ability of respondents according to the recapitulation of respondents categorized Agree where asmany as 57 people or 57% said Agree (S) and 7 or 7.40% did not agree.Simultaneous testing showed that simultaneous Motivation, Work Environment and Work Ability positive andsignificant impact on the performance PT. Pengadain (Persero) Regional Office II PekanbaruPartial test results, motivation, work environment and the ability to significantly influence the performance ofwork in PT Pengadain (Persero) Regional Office II PekanbaruKeywords: Motivation, Ability, Work Environment, Performance